Comparative effects of composting and vermicomposting on quality of organic amendments prepared from MSW and nitrogen rich Guatemala plant residues. (2017) - Pramanik, Prabhat; Ahmed, Chamim S.; Bhagat, Rajiv M.
High heavy metal contents and low nutrient status limit municipal solid waste (MSW) application in agricultural fields. In this study, high nitrogen (N) containing plant residues of Guatemala were mixed with MSW to evaluate its effect on quality of final composts and vermicomposts. Composting leads to 49.9-56.3% organic C loss from organic substrates; while 53.0-62.1% organic C was lost during vermicomposting of same treatments. In this study, total N content was increased up to 75.2-100.7% and 94.4-135.0% during composting and vermicomposting, respectively. Vermicomposts had lower heavy metal contents than composts. Mixing of Guatemala with MSW leads to the significantly higher total N content in the final product and reduced heavy metal contents only during vermicomposting. Therefore, 20% mixing (w/w basis) of N-rich plant residues with MSW may be effective to improve quality of organic amendments through vermicomposting.